Effects of yacon-derived fructooligosaccharide on the properties of yogurt - Ilagan, Maltbey Villaruel; Villarino, Blanca J. (2009.)
ABSTRACT The study was conducted to determine the effect of Yacon [Smallanthus sonchifolius] powder as a prebiotic component of yogurt. Three levels (0.5%, 1.0% 1.5% w/v) of Yacon powder added to yogurt were tested. The microbial quality, physicochemical characteristics and sensory acceptance of the yogurt samples were evaluated. The viability of lactic acid bacteria (LAB) in days 0, 3, and 7 in the yogurt samples was also determined. The microbial test indicated that the yogurt samples had low mesophilic aerobes (< 4 log CFU/mL) and yeasts and molds growth and thus safe for consumption. Additionally, pH, color, titrable acidity, soluble solids and viscosity of all the yogurt samples were comparable to established parameters for yogurts. The consumer acceptance tests indicated that yogurts supplemented with fructooligosaccharide (FOS) showed no significant difference (p>0.05) from the untreated yogurt (control). Finally, LAB showed greater viability at higher fructooligosaccharide content and on day 7, the LAB counts for the yogurts with FOS showed no significant differences (p>0.05). The results indicate that Yacon-derived FOS can be used to produce yogurts which are comparable to commercially available samples and will render greater viability of LAB.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tubers; Yogurt; Yacon